Insight. Intermediate: student's book - Wildman J. Jayne (Oxford Exam Support)
The insight Student's Book is a core component of the course, providing everything your students need to engage with their language learning in the classroom. The interesting and thought-provoking topics in the Student's Book are based on actual facts and real-life events that students can find out more about at home. The lively and attractive design combined with cutting edge content and integrated video and audio material will appeal to digital, media aware and tech-savvy teenagers. Vocabulary is widely explored through the coherent and systematic vocabulary syllabus, the Vocabulary insight pages, and the ten-page Vocabulary bank. Strategy boxes in every unit help students gradually develop their skills by working on specific aspects of grammar and vocabulary in each unit, e.g. identifying paraphrase, taking notes, and writing opening sentences.